METHODOLOGY OF FORMING THE COMPETENCE OF FUTURE TEACHERS - Sultansaidova Mushtari Abzalkhanovna (Web of Journals Publishing, 2024)
This article analyzes the views on the methodology of formation of competence of future educators.
Keywords: educator, profession, methodology, criterion, person, task, education, competence.